Prospecção química e biológica do fungo endofítico Saccharicola sp. isolado de Eugenia jambolana - Honório, Alana Evangelista [UNESP] (2013)
The proposed project's main objective is to obtain bioactive substances from chemical and biological study of the crude extract produced by the endophytic fungus Saccharicola sp. isolated from the stem of the plant species Eugenia jambolana. The crude extract was analyzed by 1H NMR and HPLC-DAD, aiming at assessing the chemical profile and thus define the methodology for isolation of substances. Next, the crude extract was subjected to chromatographic and spectrometric techniques for the isolation and structural determination of individual substances, respectively. One of the isolated substance is unique, with skeleton also unprecedented in the literature, which was produced in large quantities, and another one known as anofinic acid belonging to the class of chromenes, with few studies in the literature, and by ESI-MS were identified substances 4-hydroxy-3-prenilbenzóico acid, 4-hydroxy-3-(3-methyl-3-buten-1-yl) benzoic acid, 2,2-dimethyl-2H-chromene-6-carboxylic acid plus three others belonging to the class of novel substance.